2020
DOI: 10.1111/petr.13871
|View full text |Cite
|
Sign up to set email alerts
|

Surgical complications in pediatric kidney transplantation—Incidence, risk factors, and effects on graft survival: A retrospective single‐center study

Abstract: The field of pediatric kidney transplantation remains challenging due to an ongoing lack of size‐matched grafts and anatomical peculiarities. In the current study, we investigated the incidence of surgical complications in pediatric recipients, with a focus on risk factors and effects on graft outcome. We retrospectively reviewed all 2386 kidney transplantations at our institution from January 2005 until December 2018. Of these, 221 transplants were performed in pediatric recipients, defined as under the age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 55 publications
1
11
0
1
Order By: Relevance
“…This might be caused by the mechanical trauma induced by stent placement which activates latent BK virus (148). However, other studies showed ureteral stenting to be protective against urological complications such as stenosis or leakage (149,150). In adults stents are commonly used and associated with a reduction in urological complications from 7 to 1.5% (151).…”
Section: Surgical Complications Urological Complicationsmentioning
confidence: 99%
See 3 more Smart Citations
“…This might be caused by the mechanical trauma induced by stent placement which activates latent BK virus (148). However, other studies showed ureteral stenting to be protective against urological complications such as stenosis or leakage (149,150). In adults stents are commonly used and associated with a reduction in urological complications from 7 to 1.5% (151).…”
Section: Surgical Complications Urological Complicationsmentioning
confidence: 99%
“…A Cochrane Review in the adult population showed that early removal (<15 days) of bladder indwelling and per-urethral stents might decrease the risk on UTI, however differences are small (153). The benefits of stenting in the pediatric populations remain unclear, currently many centers chose early stent removal in order to prevent urological complications and limit the number of infectious events (72,149). The use of suprapubic bladder catheter or transurethral catheter is also based on individual preference and specific patient characteristics.…”
Section: Surgical Complications Urological Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Small donor arteries and veins, and a delicate vascular anastomosis contribute to increased thrombotic events [2,3]. Other complications, such as postsurgical bleeding because of the use of prophylactic anti-coagulation and urinary leaks, may occur [4]. Moreover, the reduced mass of SPD kidneys may lead to an imbalance between donor and recipient body size, and may be associated with an inadequate kidney function and possibly reduced graft survival because of hyperfiltration injury [5,6].…”
Section: Introductionmentioning
confidence: 99%